(untitled) (Ius Novum, 2022)
The article discusses the issues concerning the influence of the Polish legislative power on the functioning of the Constitutional Tribunal that started in the autumn of 2015. The analysis covers all legal acts passed between 2015 and 2017 that introduced changes in the structure and functioning of the Constitutional Tribunal and modified the status of its judges. The research made use of the innovative method devised by Professor Paweł Chmielnicki, which consists in the examination of substantial sources of law, i.e. real reasons for passing a given statute. The analysis covers, inter alia, materials developed by a group of specialists, including the author, employed by the Centre for Legislative Process Research at Lazarski University. The article shows that the changes in the Constitutional Tribunal do not serve to exercise citizens’ rights. They aim to strengthen the political authorities (the Parliament and its emanation, the Government) at the judicial power expense. It matches the general tendency visible after the 2015 parliamentary election targeted at weakening the position of the judiciary and personal influence of the legislative on this power. The activities do not follow the constitutional rule of separation of powers and are in conflict with the principle of separation and independence of courts and tribunals guaranteed by the Constitution. Taking into account the fact that authorities change in the conditions of a democratic system, the only panacea for the restoration of the shape and prestige of the Constitutional Tribunal is the change of the authorities. There will be an opportunity for that in the autumn of 2023.